Prevalence and Risk Factors of Coronary Heart Disease in Nawabshah: A Case-Control Study: Prevalence and Risk Factors of Coronary Heart Disease - Jamali, Yasir Akbar; Kazi, Sadia; Chandio, Mehwish Noor; Nabeel, Sobia Khan; Kanhar, Ahmed Ali; Riaz, Uzma; Iqbal, Jawed; Suhag, Ahmed Hussian; Aziz, Ijaz (Pakistan Journal of Health Sciences, 2024)
One of the top causes of mortality globally was Coronary Heart Disease (CHD), and South Asian nations were exhibiting a particular trend in this regard. Objective: To determine the prevalence and identify its associated risk factors in the Nawabshah population. Methods: For ten months, from October 5, 2023, to May 27, 2024, this case-control research was carried out at the Peoples University of Medical and Health Sciences Hospital in Nawabshah. The participants underwent a complete clinical assessment, including laboratory testing, physical examination, and medical history review. Based on known diagnostic criteria such as Electrocardiogram (ECG) analyses, cardiac enzyme levels, and imaging examinations, the attending physicians diagnosed Coronary Heart Disease (CHD). Results: In the study population, 52.5% of the cases were classified as obese, and 64.3% had hyperlipidaemia. Additionally, 31.1% of the patients in the case group had diabetes, 66.4% were smokers, and 73.5% had hypertension. Physical inactivity was prevalent in 55.5% of the patients in the case group. According to the sex distribution, there were more women in the case group (53.4% versus 45.0%). Conclusions: The high prevalence of hypertension, hyperlipidaemia, obesity, and smoking in Nawabshah is one of the modifiable risk factors for coronary heart disease that this research emphasizes. Public health measures that aim to improve people’s lifestyles and prevent diseases should be implemented immediately considering these results.